A novel assay for studying the involvement of blood cells in whole blood thrombin generation. (30th March 2020) - Wan, Jun; Konings, Joke; Yan, Qiuting; Kelchtermans, Hilde; Kremers, Romy; de Laat, Bas; Roest, Mark
Abstract: Background: Fluorogenic thrombin generation (TG) assays are commonly used to determine global coagulation phenotype in plasma. Whole blood (WB)‐TG assays reach one step closer to physiology by involving the intrinsic blood cells, but erythrocytes cause variable quenching of the fluorescence signals, hampering its routine application. Objective: To develop a new assay for continuous WB‐TG measurement. Methods: In the new WB‐TG assay, the erythrocyte‐caused distortion of signal was solved by continuously mixing the sample during the measurement. The assay was validated by evaluating the reproducibility and comparing with the paper‐based WB‐TG assay. Reconstituted human blood and WB from 119 healthy donors was tested to explore the influences of hematocrit and platelet count on TG. Results: This novel WB‐TG assay showed good reproducibility while being less affected by contact activation compared with the previous paper‐based assay. Reconstitution experiments showed that the lag time of TG was shortened by the addition of platelets but not erythrocytes. Increasing hematocrit strongly augmented the peak thrombin, even in the presence of high platelet counts. The lag time and peak of WB‐TG of 119 healthy donors were positively related to erythrocyte count after adjusting for age, sex, and oral contraceptive use with multiple linear regression analyses. The reference range and interindividual variation of WB‐TG were determined in the healthy cohort. Conclusions: A novel WB‐TG assay was developed, which is a straightforward tool to measure the involvement of platelets and erythrocytes in TG and may assist the research of blood cell‐associated coagulation disorders.